1997
DOI: 10.1038/bjc.1997.389
|View full text |Cite
|
Sign up to set email alerts
|

Effects of iron supplementation and ET-18-OCH3 on MDA-MB 231 breast carcinomas in nude mice consuming a fish oil diet

Abstract: Summary Lipid peroxidation products can be cytotoxic. Our objectives were (1) to use two pro-oxidants (iron and a pro-oxidative drug) to selectively increase lipid peroxidation in the implanted human breast tumours of mice consuming fish oil and (2) to kill the cancer cells without harming normal host tissues. The theoretical basis for selective cytotoxicity is that normal cells are better able to handle oxidative stress than cancer cells. Male athymic nude mice, consuming an AIN-76 diet, were injected s.c. wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 19 publications
1
20
0
Order By: Relevance
“…(c) The suppression in cancer growth is eliminated by antioxidants, and this elimination is proportional to the inhibition of lipid peroxidation products by antioxidants (18, 24-26, 28, 29, 33, 35, 36). (d) Although therapeutic mechanisms are not always relevant to etiology, marine n-3 fatty acids have been shown to enhance the cancer-killing effect of several chemotherapeutic drugs, and this is thought to be achieved through increased lipid peroxidation or lipid peroxidation -related mechanisms (37,(39)(40)(41)(42)(43)(44)(45). We also have supporting evidence in humans implicating the peroxidation products of marine n-3 fatty acids as the proximal anticarcinogens (46).…”
Section: Evaluation Of the Experimental Evidence In Breast Carcinogenmentioning
confidence: 57%
See 1 more Smart Citation
“…(c) The suppression in cancer growth is eliminated by antioxidants, and this elimination is proportional to the inhibition of lipid peroxidation products by antioxidants (18, 24-26, 28, 29, 33, 35, 36). (d) Although therapeutic mechanisms are not always relevant to etiology, marine n-3 fatty acids have been shown to enhance the cancer-killing effect of several chemotherapeutic drugs, and this is thought to be achieved through increased lipid peroxidation or lipid peroxidation -related mechanisms (37,(39)(40)(41)(42)(43)(44)(45). We also have supporting evidence in humans implicating the peroxidation products of marine n-3 fatty acids as the proximal anticarcinogens (46).…”
Section: Evaluation Of the Experimental Evidence In Breast Carcinogenmentioning
confidence: 57%
“…(b) This suppression in cancer growth is enhanced by pro-oxidants (iron and drugs that increase lipid peroxidation; refs. 24,29,[35][36][37][38]. (c) The suppression in cancer growth is eliminated by antioxidants, and this elimination is proportional to the inhibition of lipid peroxidation products by antioxidants (18, 24-26, 28, 29, 33, 35, 36).…”
Section: Evaluation Of the Experimental Evidence In Breast Carcinogenmentioning
confidence: 99%
“…Thus 2% AAFA TM in the diet reduced the side effects of CPT-11 treatment in mice. We have reported that supplementing the diet of mice with fish oil increased the efficacy of edelfosine against MDA-MB 231 human breast cancer (Hardman et al, 1997), doxorubicin against A549 human lung cancer (Hardman et al, 2000) and CPT-11 against MCF-7 human breast cancer (Hardman et al, 1999a). Other investigators have found that supplementing the diet with omega-3 fatty acids increased the efficacy of: epirubicin against rat mammary tumours (Germain et al, 1999) and cyclophosphamide (Shao et al, 1997) or mitomycin (Shao et al, 1995) against MX-1 human mammary tumours.…”
Section: Incell Aafamentioning
confidence: 92%
“…Studies in cell culture and animal models have shown that DHA and eicosapentaenoic acid (20:5, n-3) inhibit tumorigenesis (15,16) and the growth of rodent tumors (17,18) and human breast cancer xenografts (19,20). Importantly, n-3 polyunsaturated fatty acids selectively inhibit tumor cell proliferation and are significantly less toxic towards normal cells (21,22). DHA increases lipid peroxidation within cells (23), and the anticancer effects of DHA are blocked by the antioxidant vitamin E, indicating that oxidation plays a role in DHA's mechanism of action.…”
Section: Introductionmentioning
confidence: 99%